An N-terminal deletion variant of HCN1 in the epileptic WAG/Rij strain modulates HCN current densities - Wemhöner, Konstantin; Kanyshkova, Tatyana; Silbernagel, Nicole; Fernandez-Orth, Juncal; Bittner, Stefan; Kiper, Aytug K.; Rinné, Susanne; Netter, Michael F.; Meuth, Sven G.; Budde, Thomas; Decher, Niels (Frontiers in Molecular Neuroscience, 2015)
Rats of the Wistar Albino Glaxo/Rij (WAG/Rij) strain show symptoms resembling human absence epilepsy. Thalamocortical neurons of WAG/Rij rats are characterized by an increased HCN1 expression, a negative shift in Ih activation curve, and an altered responsiveness of Ih to cAMP. We cloned HCN1 channels from rat thalamic cDNA libraries of the WAG/Rij strain and found an N-terminal deletion of 37 amino acids. In addition, WAG-HCN1 has a stretch of six amino acids, directly following the deletion, where the wild-type sequence (GNSVCF) is changed to a polyserine motif. These alterations were found solely in thalamus mRNA but not in genomic DNA. The truncated WAG-HCN1 was detected late postnatal in WAG/Rij rats and was not passed on to rats obtained from pairing WAG/Rij and non-epileptic August Copenhagen Irish (ACI) rats. Heterologous expression in Xenopus oocytes revealed 2.2-fold increased current amplitude of WAG-HCN1 compared to rat HCN1. While WAG-HCN1 channels did not have altered current kinetics or changed regulation by protein kinases, fluorescence imaging revealed a faster and more pronounced surface expression of WAG-HCN1. Using co-expression experiments, we found that WAG-HCN1 channels suppress heteromeric HCN2 and HCN4 currents. Moreover, heteromeric channels of WAG HCN1 with HCN2 have a reduced cAMP sensitivity. Functional studies revealed that the gain-of-function of WAG-HCN1 is not caused by the N-terminal deletion alone, thus requiring a change of the N-terminal GNSVCF motif. Our findings may help to explain previous observations in neurons of the WAG/Rij strain and indicate that WAG HCN1 may contribute to the genesis of absence seizures in WAG/Rij rats.